APOE Genotype Affects Black-White Responses of High-Density Lipoprotein Cholesterol Subspecies to Aerobic Exercise Training - Obisesan, Thomas O. (2008)
OBJECTIVES: To determine whether ethnicity interacts with the APO E genotype to influence conventionally-measured high density lipoprotein cholesterol (HDL-C) subfraction levels and Nuclear Magnetic Resonance measured (HDL(NMR)-C) particle size at baseline, after training, and changes with training. METHODS: After a 6-week dietary stabilization period, men and postmenopausal women 50-75 yrs old underwent baseline testing (NMR lipid, VO(2)max, body composition, and genotyping assessments). Tests were repeated after completing 24 wks of endurance exercise-training. RESULTS: At baseline, APO E2/3 Blacks had significantly larger particle size (P<0.001) and higher total HDL(NMR)-C particle concentration (P=0.006) than Whites. After 6 months of endurance exercise-training, APO E2/3 Blacks maintained a significantly larger HDL(NMR)-C particle size (P<0.001), and particle concentration of the large HDL(NMR)-C than APO E2/3 Whites (P<0.001). In multivariate ANOVAs adjusted for demographic and environmental confounding factors, and training-induced changes in lean body mass and intra-abdominal fat; the model explained ∼33 percent of the observed variability in training-induced improvements in HDL(NMR)-C particle size (P=0.002), with APO E2/3 Blacks having a greater increase in training-induced changes in HDL(NMR)-C particle size. In a separate but similarly adjusted model for conventionally-measured HDL(2)-C, the model explained, ∼49 percent of the observed variability in training-induced changes in HDL(2)-C. CONCLUSION: Ethnicity interacted with the E2/3 genotype at the APO E gene locus to influence higher baseline, after training, and greater exercise training-induced improvements in the advantageous HDL-C subfractions in Blacks than in Whites. APO E2/3 Blacks may benefit more from aerobic-fitness to reduce CVD risk.